Reestructuración comercial administrativa con inclusión de personas con discapacidad en la empresa Mercado Libre Colombia Ltda (2019)
An administrative commercial restructuring was carried out with a focus on corporate social responsibility, in order to integrate the use of various tools acquired in the course of Industrial Engineering, to generate a contribution to Colombian society, with special emphasis on population that is significantly disadvantaged in terms of job opportunities, such as people with disabilities, with special focus on those with paraplegia or hearing impairment.